Investigating water quality dynamics and watershed-based control factors using intensive field survey and GIS the case of Estero de Valencia , Manila, Philippines - Hak, Danet
This research primarily aims to characterize factors affecting water quality and to uncover the relationship between catchment-based factors and the observed water quality variations through a GIS-based spatio-temporal analysis and statistical analysis. Intensive field surveys for flow and water quality including monthly and diurnal (24-hours) survey have been conducted in Estero de Valencia (EDV). The results of flow and water quality survet were then used to visualize the spatio-temporal variation of estero water quality. Multiple Factor Analysis (MFA), a statistical method, was later on applied to reveal the relationship between water quality variation and catchment-based control factors and the interrelation among water quality parameters. Waste generation and sanitary facility questionnaires survey have been conducted in 22 barangays of the study area in order to discover the impact of waste generation and management practice of the local community on the estero water quality and to get insights on how the improvement of estero water quality can be carried out at community level. The result of this study reveal that the concentration of the water quality parameters, including BOD, COD, Nutrients and some heavy metals were higher in the downstream than that in the upstream area. The spatial variation of TDS concentration seemed to have the same trend with that of Salinity and Conductivity which ere higher in the downstream area which is closer to the sea indicating that the variation of TDS ws affected by tidal variation. DO concentration along the estero, on the average, ranged from 1.5 mg/L to 2 mg/L except at the upstream area (with denser drainage network) where the average concentration of DO was approximately 3mg/l. This is an indication of the more or less positive effect of drainiage water estero quality. The variation of ORP along the estero was, on the average, in range of -81 mV to -210 mV. The absolute value of ORP tend to be lower in the upstream station and progressively increased toward the downstream stations. This agreed with the variation trend of DO and others water quality parameters that estero water quality was more polluted in the downstream area. However, Total and Fecal Coliform concentration in the upstream area were approximately 2 times higher that at the downstream station and this were found to be affected by the discharge of black water from the informal settlers along the estero bank.